Auxiliary Source Sizing for Hybrid Electric Vehicle - Kanchan Yadav, Swapnil Srivastava and Sanjay Kumar Maurya (International Journal of Advanced Science and Technology, 2020)
This paper presents the sizing methodology for the energy storage system of the hybrid vehicle. The power demand of vehicle should be able to overcome all the opposition forces in the movement of the vehicle. Further, this power is divided into steady and dynamic power. In hybrid vehicle power demanded is delivered by both the means of sources that are main and auxiliary. The main source delivers the steady power and the auxiliary source delivers the dynamic power. The sizing of auxiliary source methodology uses the state of charge (SOC) window from 08. to 0.6 for the optimum life cycle of the battery.  The vehicle having common drive cycle with a different auxiliary source such as Lead-acid and NiMH is used in the simulation.  The simulation results show appreciating results in term of SOC variation with the time. Further, the auxiliary source can be chosen depending on the drive condition of the vehicle..